Risiko Underweight pada balita terakhir di Rumah Tangga - Muljati, Sri; Budiman, Basuki (Lembaga Penelitian Universitas YARSI, 2008)
Household health survey and covering all 30 provinces had assessed child nutritional status(underweight) for age 1-59 months, with cut-off point <-2.00 SD. A total sample of 1714 children aged 1-59 months was included in the assessment. The objective of this study was to analyze child nutritional status and factors related to the status. The study revealed that the prevalence of underweight in Indonesia was higher than those of Malaysia or China.Multivariate analysis identified various factors that associated with the prevalence ofunderweight. Children aged 1-59 months with higher risk of underweight were those head offamily age, birth order of children and head of family education. Odd Ratio (OR=1.35), thosewhose head of family age <25 year and had education less than senior high school (OR=1.25),and birth order of children (OR=1.18). Strategies to improve nutritional status of childrenshould include accelerate nutrition intervention programs, improving carrying knowledge/practice for children and community development.